2018
DOI: 10.1177/0003489417751472
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Voice- and Swallowing-Related Symptoms After Thyroidectomy: One-Year Follow-Up Study

Abstract: Voice- and swallowing-related discomfort in patients who received thyroidectomy showed dynamic changes over time. There was a significant difference in the degree of change according to clinicopathological factors. Patients with these risk factors may benefit from appropriate patient education and various rehabilitation programs for symptom relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 17 publications
3
26
2
8
Order By: Relevance
“…As expected, this group of patients had a higher number of symptoms in both functions compared to those whose self-assessment was positive. This result is in line with the literature, indicating that voice (1,11,(14)(15)(16)(18)(19)(20)(21) and swallowing (1,4,(13)(14)(15)(16)(17)(21)(22)(23) symptoms may be reported by patients referred for thyroidectomy. This is especially due to the compressive characteristics of thyroid disease, in addition to hormonal changes and impairment of laryngeal mobility or laryngotracheal complex (1,4) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, this group of patients had a higher number of symptoms in both functions compared to those whose self-assessment was positive. This result is in line with the literature, indicating that voice (1,11,(14)(15)(16)(18)(19)(20)(21) and swallowing (1,4,(13)(14)(15)(16)(17)(21)(22)(23) symptoms may be reported by patients referred for thyroidectomy. This is especially due to the compressive characteristics of thyroid disease, in addition to hormonal changes and impairment of laryngeal mobility or laryngotracheal complex (1,4) .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is recommended that voice complaint be especially valued before thyroidectomy, as it may indicate the presence of multiple symptoms. Overall, the results of this study corroborate that patient perception seems to be an important measure in swallowing (8,12,15,17,(21)(22)(23) and voice (8,10,15,(19)(20)(21)(22)(23) assessment, as it can report subjective aspects not considered by the evaluator (17,19) . Based on the results, it can be inferred that swallowing and voice self-assessments should be considered in the care of patients referred for thyroidectomy, mainly because complaints in these two functions may appear concomitantly.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, there is significant variability in the methods employed, especially with regard to the most adequate period for performing the evaluations [8,13,27,28]. It is evident that, regardless of how long after surgery the postoperative evaluation occurs -2 h; 1 day; on the 7th, 12th, or 60th day; 1, 3, or 6 months; or 4 years [6,15,24,27,29,[30][31][32][33][34][35] -the presence of upper airway, vocal and/or swallowing sensory disorders is found, suggesting that this alteration is not directly related to the existence of complications due to intubation, although Peppard and Dickens (1983) [36] and Pereira et al (2003) [24] reported that swallowing function can be altered due to the modification of the sensitivity of the intraoral, pharyngeal, and laryngeal region resulting from intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngolaryngeal symptoms are common after thyroidectomy (1)(2)(3)(4) and generally relate to the involvement of the recurrent or superior laryngeal nerve during surgery (1) . However, symptoms such as difficulties in swallowing and vocal changes can occur even in the apparent absence of nerve damage.…”
Section: Introductionmentioning
confidence: 99%
“…Compressive and vocal symptoms such as hoarseness, difficulty in swallowing, and pharyngeal globus also occur prior to surgery (1,(2)(3)(4)(5) due to hormonal disorders, enlarged thyroid gland, or the presence of benign or malignant nodules (1,3) .…”
Section: Introductionmentioning
confidence: 99%